Penerapan Kecerdasan Buatan untuk Meningkatkan Pembelajaran Desain Logo dalam Industri Kreatif - Muhammad Tahsin; Putri Latiffa Azzahra (Design Journal, 2024)
The integration of Artificial Intelligence (AI) into logo design education represents a pivotal advancement within the creative industry, aiming to enhance both pedagogical strategies and practical design applications. This study seeks to explore how AI-based platforms can improve the learning experience by fostering creativity and expanding students' design capabilities. Using a mixed-method approach combining qualitative and descriptive methods, this research analyzes multiple AI logo generator platforms—such as Canva, Adobe Logo Maker, and Wix Logo Maker—and their effectiveness in both education and industry. Data were collected through literature reviews, case studies, and interviews with users to gain comprehensive insights into AI’s impact on the design process. The findings indicate that AI-based education offers significant benefits, including improved efficiency and faster production, which align with market demands. Platforms such as Canva and Wix were particularly effective for beginner students, while Adobe Logo Maker and LogoAI provided professionals with deeper control and customization options. However, the research also highlights challenges related to the ethical use of AI, including data security concerns and the balance between automation and human creativity. The study concludes that AI-based education equips students with essential design skills, preparing them to meet future industry challenges.